The Influence of Brand Trust, Brand Identification, Brand Involvement, and Brand Commitment on Brand Evangelism - Anindita Imam Basri; Syahri Alkaf Hidayat; Bryan Ramadan; Kasnowo Kasnowo (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to identify factors that influence brand evangelism at Bank Syariah Indonesia (BSI). This study uses a quantitative model with independent variables consisting of brand trust, brand identification, brand involvement, and brand commitment, and the dependent variable is brand evangelism. The sampling technique used is purposive sampling, with 140 Bank Syariah Indonesia customers as respondents who filled out the questionnaire via Google Form. Data analysis was carried out using multiple linear regression. The results showed that all independent variables had a positive and significant effect on brand evangelism. The brand trust variable has the greatest influence with a regression coefficient value of 0.435, while brand identification has the smallest influence with a coefficient value of 0.232. This shows that consumer trust in BSI is a dominant factor in encouraging them to recommend or promote the brand to others. The implications of this study are valuable information for the financial services sector, especially Islamic banks, to focus on increasing customer trust as a strategy to strengthen brand loyalty and advocacy.